Communication With Significant Others About Weight Management: The Role of Confirmation in Weight Management Attitudes and Behaviors - Dailey, René M. and Richards, Andrea A. and Romo, Lynsey Kluever (Communication Research, 2010)
The current study employed a confirmation perspective to examine the relationship between communication with significant others and individuals’ weight management. Confirmation was conceptualized as consisting of two components—acceptance and challenge. In Study 1, 413 participants (aged 18-66) completed a survey assessing their diet and exercise behaviors as well as interactions with a significant other about weight management. As predicted, the combination of acceptance and challenge from significant others was related to the highest levels of body self-esteem, eating and exercise self-efficacy, and healthy eating behaviors beyond the individual effects of acceptance and challenge. In Study 2, 161 participants (aged 18-62) rated the effectiveness of messages varying in acceptance and challenge. Messages higher in both acceptance and challenge were rated as more effective in motivating healthy behaviors than messages primarily higher in either acceptance or challenge or lower in both. Overall, both studies suggest the contribution of one component of confirmation was enhanced by the presence of the other component in predicting weight management attitudes and behaviors.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjEwMzYyNjg4